2018
DOI: 10.3390/en11040704
|View full text |Cite
|
Sign up to set email alerts
|

Methodology for the Study of the Envelope Airtightness of Residential Buildings in Spain: A Case Study

Abstract: Air leakage and its impact on the energy performance of dwellings has been broadly studied in countries with cold climates in Europe, US, and Canada. However, there is a lack of knowledge in this field in Mediterranean countries. Current Spanish building regulations establish ventilation rates based on ideal airtight envelopes, causing problems of over-ventilation and substantial energy losses. The aim of this paper is to develop a methodology that allows the characterization of the envelope of the housing sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 27 publications
(39 reference statements)
0
18
0
Order By: Relevance
“…The corresponding graphs were obtained and there was an n 50 air infiltration value of 50 Pa. To characterise the information obtained, the Minneapolis Blower Door Model 3 software (TEC-TITE 5.0) was used. This tool was developed specifically to describe 140 parameters that possibly intervene in the filtration phenomenon [55]. These parameters were collected in a database used to perform a general evaluation of the results.…”
Section: Air Infiltration Through the Envelopementioning
confidence: 99%
“…The corresponding graphs were obtained and there was an n 50 air infiltration value of 50 Pa. To characterise the information obtained, the Minneapolis Blower Door Model 3 software (TEC-TITE 5.0) was used. This tool was developed specifically to describe 140 parameters that possibly intervene in the filtration phenomenon [55]. These parameters were collected in a database used to perform a general evaluation of the results.…”
Section: Air Infiltration Through the Envelopementioning
confidence: 99%
“…A number of studies have been conducted on airtightness in single-family homes in northern Europe [2][3][4][5][6] and the United States [7][8][9] over the last three decades. It has also been an emerging field of research over the last 10 years in southern Europe, Spain included [10][11][12][13][14], where the Infiles research project [15] presently underway has been enlarging the country's airtightness database [16][17][18][19][20] using a standardised measuring protocol to ensure comparability of the findings.…”
Section: Introductionmentioning
confidence: 99%
“…The most significant energy losses occur through the envelope, due poor insulation, ventilation, and infiltration. Additionally, studies have shown that losses due to air leaks can generate problems of lower thermal comfort, in addition to a deterioration in ventilation systems [5].…”
Section: Introductionmentioning
confidence: 99%
“…Methods have been developed to determine the building air change rate (ACR) in residential buildings [1] and its impact on the energy performance studied within cold climate countries [5]. The most widespread technique used is the blower door test that quantifies the flow of air due to losses when a pressure difference is applied in a sealed building.…”
Section: Introductionmentioning
confidence: 99%